Evaluation of Serum Clusterin Levels in Type 2 Diabetic Men with and without Cardiovascular Disease - Fayez, Safa S.; Rashied, Rashied. M.; Al-Alaaraji, Shakir F.T. (Iraqi Journal of Science, 2020)
Objectives: The objective of this study was to evaluate serum levels of clusterin (CLU) in type 2 diabetics with and without cardiovascular disease and to explore possible correlations with insulin resistance and related progression of cardiovascular disease in Iraqi men.Methods: Sixty-three T2DM patients, including forty-two with cardiovascular disease (CVD), were divided into three subgroups; twenty-one with myocardial infraction (MI), twenty-one with other CVD, and twenty-one without any cardiac complication. In addition, a group of twenty-one men served as healthy controls (HCs) for comparison purposes. The four groups were analyzed for parameters that included fasting serum glucose (FSG), lipid profile, fasting serum insulin (FSI), homeostasis model assessment of insulin resistance (HOMA-IR), cardiac Troponin-I (cTn-I), CK-MB, and some other biochemical variables.Results: Our results showed that the serum CLU levels were higher in T2DM with MI than the other groups of patients, while the levels were significantly elevated in the entire T2DM group as compared to the control group. Serum levels of CLU showed significantly positive correlations with cTn-I and CK-MB (r= 0.658 p < 0.01and r = 0.575, p < 0.01 , respectively), whereas the correlation with HDL-C was negative. However, the other parameters exhibited weak correlations with serum CLU levels.Conclusions: CLU participates in the event of cardiovascular disease and insulin resistance in Iraqi males with T2DM and may be used as predictor for CVD development in T2DM patients.